Experiencia de dermatitis atópica en el Hospital Infantil de Morelia "Eva Sámano López Mateos" - Espinoza Azpeytia, Aurora Irene (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
Analyze the frequency, risk factors and treatment of atopic dermatitis in de pediatric population of the children´s Hospital of Morelia for 18 months. MATERIAL AND METHODS: study of retrospective prevalence, with the review of files reported in the daily sheets of extern consult of pediatric dermatology with the diagnosis of atopic dermatitis, from January 2018 to June 2019. Results: The atopic dermatitis in the children´s hospital of Morelia have an incidence of 5.67% in the pediatric dermatology consultation, with freater incidence in women won a 55%. The most affected age group was preschoolers with the 29.7%. The distribution of AD by municipality was reported in 80% of patients in Morelia. The personal atopic factors were presented in 20% of the patients, reported asthma, rhinitis and food allergy with 20% of each. The atopic family risk factors were presented in 8.1% of the patients, being asthmatic mothers the most common with a 50%. The upper limbs were the most affected of all the patients with a 24.3% of the cases. The associated comorbidities were presented in a 20% of the patients being the most common the obesity with a 25%. For the treatment the most used was the emollient as monotherapy in a 32.4%. The 53% of the files were eliminated because the patients only have 1 consultation, the rest of the patients, the 25% had an unfavorable evolution being in a 55.6% of the cases for not going to consultation. DISCUSSION: The reported data of age and sex coincide with the reported by the world and national literature. The association with atopic diseases both family and personal we are well below in comparation with the reported.

Analizar la frecuencia, factores de riesgo y tratamiento de la dermatitis atópica en la población pediátrica del Hospital Infantil de Morelia durante 18 meses. MATERIAL Y METODOS: Estudio de prevalencia retrospectivo, con revisión de expedientes reportados en las hojas diarias de la consulta externa de dermatología pediátrica con el diagnóstico de dermatitis atópica, de enero del 2018 a junio del 2019. RESULTADOS: La dermatitis atópica en el Hospital Infantil de Morelia reporta una incidencia del 5.67% de la consulta de dermatología pediátrica, presenta una mayor incidencia en mujeres con el 55% el grupo etario más afectado fue en de prescolares con el 29.7%. La Distribución de DA por municipio reporta un 80% de pacientes en Morelia. Los factores personales de atópica se presentaron en el 20% de los pacientes, presentando asma, rinitis alérgica y alergia alimentaria cada uno con un 20%. Los Factores de riesgo familiares de atopia se presentaron en el 8.1% de los pacientes siendo madres asmáticas el más común con un 50%. De todos los pacientes las extremidades superiores fueron las más afectadas en un 24.3% de los casos. Las comorbilidades asociadas se presentaron en un 20% de los pacientes siendo la más común obesidad en un 25%. En cuanto al tratamiento el más empleado fue el emoliente como monoterapia en un 32.4%. El 53% de los expedientes se eliminaron por acudir 1 consulta, del resto de los pacientes el 25.7% tuvo una evolución no favorable siendo el 55.6% de los casos por no acudir a consultas de seguimiento. DISCUCIÓN: Los datos reportados de edad y sexo coinciden con lo comentado por la literatura mundial y nacional. La asociación con enfermedades atópicas tanto familiares como personales estamos muy por debajo de lo reportado.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Pediatría
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4330; info:eu-repo/classification/cti/3; FCMB-E-2020-0265; Morelia; Topografía; Factores de atopia